Biological removal of pharmaceutical compounds using white-rot fungi with concomitant FAME production of the residual biomass. (15th September 2016) - Vasiliadou, I.A.; Sánchez-Vázquez, R.; Molina, R.; Martínez, F.; Melero, J.A.; Bautista, L.F.; Iglesias, J.; Morales, G.
Abstract: The efficiency of two white-rot fungi (WRF), Trametes versicolor and Ganoderma lucidum, to eliminate thirteen pharmaceutical pollutants with concomitant biodiesel production from the accumulating lipid content after treatment, was examined. The removal efficiency was studied using both individual and combined strains. The results of individual and combined strains showed a total removal (100%) of diclofenac (DCF), gemfibrozil (GFZ), ibuprofen (IBP), progesterone (PGT) and ranitidine (RNT). Lower removals were achieved for 4-acetamidoantipyrin (AAA), clofibric acid (ACF), atenolol (ATN), caffeine (CFN), carbamazepine (CZP), hydrochlorothiazide (HCT), sulfamethoxazole (SMX) and sulpiride (SPD), although the combination of both strains enhanced the system's efficiency, with removals ranging from 15 to 41%. This increase of the removal efficiency when combining both strains was attributed to the interactions developed between them (i.e., competition). Results from enzymatic and cytochrome P450 examination suggested that both extracellular (laccase, MnP, LiP) and intracellular oxidation mechanisms participate in the biological removal of pharmaceuticals. On the other hand, the "green" potential of the fungal sludge generated during the biological removal process was assessed for biodiesel production by means of one-step direct ( in-situ ) transformation. This process consists of the simultaneous extraction and conversion of lipids contained in the sludge by catalytic esterification/transesterification using a robust acid heterogeneous Zr-SBA-15 catalyst. This catalytic system provided conversions close to 80% of the saponifiable fraction (including free fatty acids and glycerides) in the presence of high amount of impurities. The overall weight FAME yield, based on the initial dried mass, was close to 30% for both strains. Graphical abstract: Highlights: The efficiency of white-rot fungi on the removal of 13 pharmaceuticals was studied. Trametes versicolor and Ganoderma lucidum, achieved 100% removal of DCF, GFZ, IBP, PGT and RNT. Both cytochrome P450 and extracellular system contributed to the biological removal. Efficient production of biodiesel from the residual fungal mass was achieved. Zr-SBA-15 catalyst converts ca. 80% of the saponifiable oil fraction into FAME.